2017
DOI: 10.12934/jkpmhn.2017.26.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Internalized Stigma in Persons with Psychiatric Disabilities

Abstract: Purpose: This phenomenological study was done to identify comprehensively and in depth the experience of overcoming internalized stigma in persons with psychiatric disabilities. Methods: Data were collected from December 2015 to June 2016 with 10 persons who had psychiatric disabilities. The participants took part in interviews on their experiences of overcoming stigma. The collected data were analyzed using Colaizzi method. Results: From the raw data obtained from the study participants, 12 themes and 5 theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the casual condition, potential threats to wellbeing during COVID-19 emerged as upper themes. Studies found negative psycho-social health consequences, including anxiety, depressive symptoms, social isolation, and loneliness due to the disease's unprecedented circumstances [18,19]. Congruent with international research, most of this study's participants reported confusion from the sudden loss of normality, not knowing what would happen, and healthcare problems during COVID-19 recovery [20].…”
Section: Discussionmentioning
confidence: 73%
“…In the casual condition, potential threats to wellbeing during COVID-19 emerged as upper themes. Studies found negative psycho-social health consequences, including anxiety, depressive symptoms, social isolation, and loneliness due to the disease's unprecedented circumstances [18,19]. Congruent with international research, most of this study's participants reported confusion from the sudden loss of normality, not knowing what would happen, and healthcare problems during COVID-19 recovery [20].…”
Section: Discussionmentioning
confidence: 73%